The sedimentary record of the Issyk Kul basin, Kyrgyzstan: climatic and tectonic inferences. (5th January 2015) - Macaulay, Euan A.; Sobel, Edward R.; Mikolaichuk, Alexander; Wack, Michael; Gilder, Stuart A.; Mulch, Andreas; Fortuna, Alla B.; Hynek, Scott; Apayarov, Farid
Abstract: A broad array of new provenance and stable isotope data are presented from two magnetostratigraphically dated sections in the south‐eastern Issyk Kul basin of the Central Kyrgyz Tien Shan. The results presented here are discussed and interpreted for two plausible magnetostratigraphic age models. A combination of zircon U‐Pb provenance, paleocurrent and conglomerate clast count analyses is used to determine sediment provenance. This analysis reveals that the first coarse‐grained, syn‐tectonic sediments (Dzhety Oguz formation) were sourced from the nearby Terskey Range, supporting previous thermochronology‐based estimates of a ca . 25–20 Ma onset of deformation in the range. Climate variations are inferred using carbonate stable isotope (δ 18 O and δ 13 C) data from 53 samples collected in the two sections and are compared with the oxygen isotope compositions of modern water from 128 samples. Two key features are identified in the stable isotope data set derived from the sediments: (1) isotope values, in particular δ 13 C, decrease between ca . 26.0 and 23.6 or 25.6 and 21.0 Ma, and (2) the scatter of δ 18 O values increased significantly after ca . 22.6 or 16.9 Ma. The first feature is interpreted to reflect progressively wetter conditions. Because this feature slightly post‐dates the onset of deformation in the Terskey Range, we suggest that it has been caused by orographically enhanced precipitation, implying that surface uplift accompanied late Cenozoic deformation and rock uplift in the Terskey Range. The increased scatter could reflect variable moisture source or availability caused by global climate change following the onset of Miocene glaciations at ca . 22.6 Ma, or enhanced evaporation during the Mid‐Miocene climatic optimum at ca . 17–15 Ma.